Enhancing Physical Performance and Health: The Effects of Withania Somnifera on Strength, Endurance, and Overall Well-being - Biliński, Karol; Korgiel, Matylda; Janota, Martyna; Tetela, Katarzyna; Gaweł-Dąbrowska, Dagmara (Quality in Sport, 2025)
Introduction: Withania Somnifera (Ashwagandha), an ancient ayurvedic remedy, has been valued for centuries in traditional medicine due to its versatility of beneficial properties on the body system. Contemporary research aims to expand the medicinal use of Ashwagandha and fully harness its adaptogenic potential. Recently, Ashwagandha has gained the rising interest of sportsmen seeking effective and natural ways to enhance their performance. Purpose of the work: The aim of this study is to review existing research on the effects of Withania Somnifera (Ashwagandha) supplementation on performance, as well as its beneficial impact on overall health and well-being of athletes. Materials and methods: A comprehensive literature search and analysis was conducted on PubMed, Google Scholar, Scopus and Science Direct databases using combinations of the following phrases: „Withania Somnifera”; „Ashwagandha”; „Adpatogens”; „Health Benefits of Ashwagandha”; „Ashwagandha and Physical Performance”; „Ashwagandha and Endurance”; „Adverse Effects of Ashwagandha”. Results: Supplementation of Ashwagandha has been demonstrated to enhance physical performance and recovery in athletes, as well as significantly improve strength and muscle mass. Furthermore, supplementation provides various health benefits for the body, with emphasis on improved sleep quality and reduced stress and anxiety. Research recognises Ashwagandha as safe and well-tolerated.